Building and Sustaining National ICT Education Agencies : Lessons from England (Becta) - Dykes, Gavin (World Bank, Washington, DC, 2017)
The British educational communications and technology agency (Becta) was established in 1998 and finally closed in 2011. The government in England set out Becta’s priorities in annual remit letters, and the agency’s changing role is traced through the content of these letters. Becta primarily addressed school-based and technical and vocational education and it acted as the key agency in taking forward England’s e-learning strategy, harnessing technology. In Becta’s lifetime, technology changed dramatically, and the agency played an important role in building the capacity of schools and colleges to support their work and the learning of students through technology. Becta played an important role in conducting research and gathering evidence in use of technology for learning and in developing education leadership and teacher capacity to use technology across the school curriculum. While every national context is different, some of the experience associated with Becta’s existence may provide a starting point for reflection on the development of similarly focused information and communication technology (ICT) in education agencies.